Flavonoids from Gutierrezia repens (Asteraceae) - Alarcón, Silvia Rosana (2007)
7,3'-dimethylquercetin 1, 7,3,3'-trimethylquercetin 2, 7,3,4'-trimethylquercetin 3 and quercetin 4 were isolated from aerial parts of Gutierrezia repens (Asteraceae). The structures of 1, 2 and 3 were determined mainly on the basis of 2D NMR data. Their 1H NMR spectra in CDCl3 and Me2CO-d6 are compared and discussed. The 13C NMR spectra of these compounds are given here for the first time.